Legal Protection Perspective of Underage Marriage - Asmara, Ayu (Universitas Negeri Gorontalo, 2022)
In Indonesia, when it comes to marriage, it is regulated that the legal age limit for marriage is 19 years for men and 16 years for women. The purpose of this study is to determine the perspective of legal protection against child marriage. This research uses normative juridical research methods, by prioritizing secondary data in the form of primary legal materials derived from laws and regulations related to the studies discussed, as well as using relevant literature. The results in this study are from the perspective of the Marriage Law, the consequences of underage marriage are clearly contrary to the purpose of marriage. With the existence of underage marriage, this indicates that Law Number 1 of 1974 concerning Marriage and Government Regulation Number 9 of 1975 concerning Regulations for the Implementation of Law Number 1 of 1974 are less effective.Â With the existence of underage marriage, there are many cases of divorce because the marriage is carried out by children who are still underage, so they cannot fully carry out the purpose of marriage as stated in the legislation.